The spatial solution is written as $$\Phi_k(r) = r^{1-\frac{d}{2}} \left(c_1 J_{1-\frac{d}{2}}(k r) + c_2 Y_{-1+\frac{d}{2}}(kr)\right).$$ In the case $d=3$, the solutions can be written as $$\Phi_k(r) = \hat{c}_1 j_0(k r) + \hat{c}_2 y_0(k r) = \hat{c}_1(k) \frac{\sin k r}{r} + \hat{c}_2(k) \frac{\cos k r}{r},$$ where $j_0$ and $y_0$ are the Spherical Bessel Functions.

My question is how $j_0$ and $y_0$ are co-related with $J_{1-\frac{d}{2}}$ and $J_{1+\frac{d}{2}}$. Canonical explanation with book reference will be helpful for me. Thanks in advance.

Reference post:Solution of a differentiation in integral form


So let's look at what you have when $d=3$. When $d=3$,

$$\Phi_k(r)=r^{-\frac{1}{2}}\left(c_1J_{-\frac{1}{2}}(kr) + c_2Y_{\frac{1}{2}}(kr)\right).$$

In similar fashion to your previous post, we know that $J_{-\frac{1}{2}}(x) = \sqrt{\frac{2}{\pi x}}\cos x $. You can prove this pretty easily using the exact same techniques as myself and the other user that answered. We also know that

$$Y_{\nu}(x) = \frac{J_{\nu}(x)\cos(\nu\pi)-J_{-\nu}(x)}{\sin(\nu\pi)}.$$

Letting $\nu = \frac{1}{2}$ we have that $Y_{\frac{1}{2}}(x) = -J_{-\frac{1}{2}}(x)$. So we see that in the case of $d=3$ that the only solution we need to concern ourselves with is $J_{-\frac{1}{2}}$.

Pursuing this, we have

$$\Phi_k(r) = Cr^{-\frac{1}{2}}J_{-\frac{1}{2}}(kr),$$

where $C = c_1-c_2$. This gives us that

$$\Phi_k(r) = Cr^{-\frac{1}{2}}\sqrt{\frac{2}{\pi kr}}\cos(kr) = -C'(k)\frac{\cos(kr)}{kr} = C'(k)y_0(kr).$$

Here I've defined $C'(k) = -\frac{C}{\sqrt{k}}$.

In the general case, $j_n(x) = \sqrt{\frac{2}{\pi x}}J_{n+\frac{1}{2}}(x)$ and $y_n(x) = \sqrt{\frac{2}{\pi x}}Y_{n+\frac{1}{2}}(x).$ From this it's clear that your solution can be written in terms of these since your Bessel functions are evaluated at half integers. I have to get to a seminar so if you have questions, I will address them later.

  • $\begingroup$ Got it thanks. :-) $\endgroup$ – Complex Guy Sep 10 '13 at 19:15

Form Arfken's Mathematical Methods for Physicist:

When the Helmholtz equation is separated in spherical coordinates, the radial equation has the form $$ R'' + \frac{2}{r} R' + \left(k^2 - \frac{n(n+1)}{r^2}\right)R = 0. \tag{1} $$ If we substitute $$ R(k r) = \frac{Z(k r)}{(k r)^{1/2}} $$ equation (1) becomes $$ Z'' + \frac{1}{r} Z' + \left(k^2 - \frac{(n + \frac{1}{2})^2}{r^2}\right)Z = 0, \tag{2} $$ which is Bessel equation. $Z$ is a Bessel function of order $n + \frac{1}{2}$ ($n$ an integer). Because of the importance of spherical coordinates, this combination, $$ \frac{Z_{n+1/2}(k r)}{(k r)^{1/2}} $$ occurs quite often.

Is convenient to label these functions as spherical Bessel functions with the following defining equations \begin{align} j_n(x) &= \sqrt{\frac{\pi}{2 x}} J_{n+1/2}(x), \\ \\ y_n(x) &= \sqrt{\frac{\pi}{2 x}} Y_{n+1/2}(x). \end{align}

Any book on Bessel functions or Special functions will have detailed relations and properties. Specifically, being $$ J_{n+1/2}(x) = \sum_{s=0}^\infty \frac{(-1)^s}{s!(s+n+\frac{1}{2})!}\left(\frac{x}{2}\right)^{2s + n + 1/2} $$ it's clear that $$ j_0(x) = \sqrt{\frac{\pi}{2 x}} \sum_{s=0}^\infty \frac{(-1)^s}{s!(s+\frac{1}{2})!}\left(\frac{x}{2}\right)^{2s + 1/2} = \frac{\sin x}{x}, $$ where we have used the Legendre duplication formula $$ s!(s+\tfrac{1}{2})! = \frac{\sqrt{\pi}}{2^{2 s + 1}}(2 s + 1)!. $$

Analogously, $$ y_0(x) = -\frac{\cos x}{x}. $$

  • $\begingroup$ Thanks your addition makes me more comfortable to get. $\endgroup$ – Complex Guy Sep 10 '13 at 19:15

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.